Intergenerational transmission of human capital in early childhood - Katja Coneus; Maresa Sprietsma (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
It is a well-known fact that the level of parents' education is strongly correlated with the educational achievement of their children. In this paper,we shed light on the potential channels through which human capital is transmitted from mothers to their children in early childhood. The main channels through which maternal human capital benefits the child's verbal and social skills are birth weight and father's support. Moreover,reading stories to the child is most relevant for the transmision of verbal skills whereas for social skills, a crucial channel for maternal human capital is the attendance of institutional childcare.
Keywords: I20; 330; early childhood; skills; intergenerational transmission; Kinder; Bildungsniveau; Qualifikation; Familiensoziologie; Generationenbeziehungen; Kinderbetreuung; Deutschland